ANALISIS PENGELOLAAN MODAL KERJA UNTUK MENINGKATKAN PROFITABILITAS PADA PT. PEMBANGUNAN ABADI ANDALAS AGUNG (PA3) DURI PERIODE 2014-2018 - Yunisha, Welda; Ibrahim, Mariaty (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
This research was conducted at PT. Development of Abadi Andalas Agung (PA3) Duri with the problem in research, namely the decline in the company's ability to obtain profitability. The purpose of this study is to analyze working capital management to increase company profitability. Types and sources of data used are primary data and secondary data from the financial statements of PT. Eternal Development of Andalas Agung (PA3) Duri for the 2014-2018 period. The data collection technique uses the method of documentation of financial statements and interviews, while the data analysis technique used by the author in this study is ratio analysis.The results showed that PT. Pembangunan Abadi Andalas Agung (PA3) calculation on the activity ratio shows that total asset turnover has fluctuated and working capital turnover has increased. The calculation of the liquidity ratio shows that the current ratio, quick ratio, and cash ratio have fluctuated. The calculation of the profitability ratio shows that the gross profit margin, net profit margin, return on assets and return on equity have fluctuated during the last five years. Keywords: Working Capital, Activities, Liquidity, Profitability